State of birth and cardiovascular disease mortality: Multilevel analyses of the National Longitudinal Mortality Study. (September 2021) - Xu, Wei; Topping, Michael; Fletcher, Jason
Abstract: Cardiovascular disease (CVD) is the leading contributor to mortality in the United States. Previous studies have linked early life individual and family factors, along with various contemporaneous place-based exposures to differential individual CVD mortality risk. However, the impacts of early life place exposures and how they compare to the effects of an individual's current place of residence on CVD mortality risk is not well understood. Using the National Longitudinal Mortality Study, this research examined the effects of both state of birth and state of residence on individual's risk of CVD mortality. We estimated individual mortality risk by estimating multi-level logistic regression models. We found that during a follow-up period of 11 years, 18, 292 (4.2%) out of 433, 345 participants died from CVD. The impact of state of birth on subsequent CVD mortality risk are greater than state of residence, even after adjusting for socio-demographic factors. Individuals who were born in certain states such as Tennessee, Kentucky, and Pennsylvania on average had higher CVD mortality risk. Conversely, those born in California, North Dakota, and Montana were found to have lower risk, no matter where they presently live. This study implies that early life state-level environments may be more prominent to individual's CVD mortality risk, compared to the state in which one lives. Future research should address specific mechanisms through which state of birth may affect people's risk of CVD mortality. Highlights: State of birth is a stronger predictor of CVD mortality than state of residence. Models including state of birth random effects better predict individual CVD mortality risk. Those born in Tennessee and Kentucky had the highest average CVD mortality risk while those born in California and North Dakota had the lowest risk. Tennessee, Kentucky, Virginia, West Virginia, and Pennsylvania are a cluster of high state of birth effects.